2008
DOI: 10.1088/0004-6256/136/3/1089
|View full text |Cite
|
Sign up to set email alerts
|

LONG-TERM PHOTOMETRIC ANALYSIS OF THE ACTIVE W UMa-TYPE SYSTEM TU BOOTIS

Abstract: We present multi-color light curves for the W UMa-type eclipsing binary TU Boo for two epochs separated by 22 years. An analysis of the O-C diagram indicates the earlier observations took place right in the middle of a major period change, thus allowing for a unique study on mass transfer and period changes in this W UMa-type system. We compute model fits to our light curves, along with the only other published set, using the Wilson-Devinney program, and find temporally correlated changes in the size of the se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
(32 reference statements)
0
11
0
1
Order By: Relevance
“…Live version of the data can be downloaded from http://www.inasan.ru/∼malkov/CEV/ APPENDIX A: DISCUSSION OF SELECTED BINARIES TU Boo may be classified as a contact W UMa of Asubtype because the primary minimum is a transit. The asymmetry of light curves was detected by several authors (Niarchos et al 1996;Coughlin et al 2008). Niarchos et al (1996) found the light curve solution with WD program using spotted model for contact configuration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Live version of the data can be downloaded from http://www.inasan.ru/∼malkov/CEV/ APPENDIX A: DISCUSSION OF SELECTED BINARIES TU Boo may be classified as a contact W UMa of Asubtype because the primary minimum is a transit. The asymmetry of light curves was detected by several authors (Niarchos et al 1996;Coughlin et al 2008). Niarchos et al (1996) found the light curve solution with WD program using spotted model for contact configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their solution with spots shows that the less massive and smaller secondary is hotter than the primary. According to Coughlin et al (2008) TU Boo is a marginal contact system with both components almost filling their critical lobes. They supposed the mass transfer from secondary to primary which is supported by an increased period.…”
Section: Appendix B: Application Of the Classification Algorithmmentioning
confidence: 99%
“…The temperature of its spotfree part may be higher than the secondary's temperature but the apparent surface averaged temperature is lower. W UMa-type stars have a very high level of chromosphericcoronal activity (Cruddace & Dupree 1984;Rucinski 1985;Vilhu & Walter 1987;Stȩpień et al 2001) and variations of the light curve, observed on time scales of decades, indicate that they also possess dark starspots covering a variable fraction of the stellar surface (Gazeas, Niarchos & Gradoula 2006;Coughlin, Dale & Williamon 2008). Perhaps the most extreme example of light curve variability due to a variable coverage by spots can be seen in Rucinski & Paczynski (2002).…”
Section: The W-type Phenomenon and Photospheric Starspotsmentioning
confidence: 99%
“…As the two components of FO Hya are in a state of over-contact, we take the most likely cause of the period change as the transfer of mass between the components. The amount of mass transfer, dm is related to the change in period, dP, for a system of total mass, M via (Coughlin et al, 2008;Yang and Liu, 2003).…”
Section: Period Analysismentioning
confidence: 99%